The Complete Evaluation of Road Accidents Losses - Žvirblis, Algis (Ekonomika, 2003)
The article deals with the problems of the complete evaluation of total losses by road accidents. The theoretical principles of special factors - transport flaws. traffic safety and volume of dangerous materials parameters influencing total loss arc analysed. Methodology of the evaluation of total losses in Lithuania including loss of GDP and social-moral expenditure also model of risk evaluation arc presented.